Oxidative stress‐induced dysregulation of excitation–contraction coupling contributes to muscle weakness. Issue 5 (2nd August 2018) - Qaisar, Rizwan; Bhaskaran, Shylesh; Premkumar, Pavithra; Ranjit, Rojina; Natarajan, Kavithalakshmi Satara; Ahn, Bumsoo; Riddle, Kaitlyn; Claflin, Dennis R.; Richardson, Arlan; Brooks, Susan V.; Van Remmen, Holly
Abstract: Background: We have previously shown that the deletion of the superoxide scavenger, CuZn superoxide dismutase, in mice ( Sod1 −/− mice) results in increased oxidative stress and an accelerated loss of skeletal muscle mass and force that mirror the changes seen in old control mice. The goal of this study is to define the effect of oxidative stress and ageing on muscle weakness and the Excitation Contraction (EC) coupling machinery in age‐matched adult (8–10 months) wild‐type (WT) and Sod1 −/− mice in comparison with old (25–28 months) WT mice. Methods: In vitro contractile assays were used to measure muscle contractile parameters. The activity of the sarcoplasmic reticulum Ca 2+ ATPase (SERCA) pump was measured using an NADH‐linked enzyme assay. Immunoblotting and immunofluorescence techniques were used to measure protein expression, and real‐time reverse transcription PCR was used to measure gene expression. Results: The specific force generated by the extensor digitorum longus muscle was reduced in the Sod1 −/− and old WT mice compared with young WT mice along with significant prolongation of time to peak force, increased half relaxation time, and disruption of intracellular calcium handling. The maximal activity of the SERCA calcium uptake pump was significantly reduced in gastrocnemius muscle from both old WT (≈14%) and adult Sod1 −/− (≈33%) mice compared with young WT mice along with increased expression of sarcolipin, a known inhibitor of SERCA activity. Protein levels of the voltage sensor and calcium uptake channel proteins dihydropyridine receptor α1 and SERCA2 were significantly elevated (≈45% and ≈57%, respectively), while the ratio of calstabin, a channel stabilizing protein, to ryanodine receptor was significantly reduced (≈21%) in Sod1 −/− mice compared with young WT mice. The changes in calcium handling were accompanied by substantially elevated levels of global protein carbonylation and lipid peroxidation. Conclusions: Our data suggest that the muscle weakness in Sod1 −/− and old WT mice is in part driven by reactive oxygen species‐mediated EC uncoupling and supports a role for reduced SERCA pump activity in compromised muscle function. The novel quantitative mechanistic data provided here can lead to potential therapeutic interventions of SERCA dysfunction for sarcopenia and muscle diseases.